2016
DOI: 10.1055/s-0042-102250
|View full text |Cite
|
Sign up to set email alerts
|

Early precut sphincterotomy for difficult biliary access to reduce post-ERCP pancreatitis: a randomized trial

Abstract: In patients with difficult biliary cannulation, early precut is an effective technique and can significantly reduce the incidence of PEP. Repeated biliary cannulation attempts are a real risk factor for this complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 24 publications
0
60
1
5
Order By: Relevance
“…The rate of PEP was significantly lower in the early PS group (5.4% vs 12.1%; OR 0.35, 95% CI 0.16 –0.78). Subgroup analysis also found that the incidence of PEP was significantly lower with early PS compared to delayed PS (5.4% vs 14.1 %; OR 0.42, 95 % CI 0.17 –1.07) . However, the impact of PEP prophylactic measures after PS has never been specifically addressed, and in fact, there was no PEP prophylaxis in this study.…”
Section: Discussionmentioning
confidence: 56%
“…The rate of PEP was significantly lower in the early PS group (5.4% vs 12.1%; OR 0.35, 95% CI 0.16 –0.78). Subgroup analysis also found that the incidence of PEP was significantly lower with early PS compared to delayed PS (5.4% vs 14.1 %; OR 0.42, 95 % CI 0.17 –1.07) . However, the impact of PEP prophylactic measures after PS has never been specifically addressed, and in fact, there was no PEP prophylaxis in this study.…”
Section: Discussionmentioning
confidence: 56%
“…The patients were randomized as early precut group and standard technique group. Lower PEP rate was observed in early precut group (5.4% vs 12.1%) . If the patient with common bile duct dilation down to the papilla, some studies suggested fistulotomy is the preferred precut technique …”
Section: Risk Factorsmentioning
confidence: 92%
“…In a prospective, multicenter, randomized clinical trial, ERCP patients with early precut for difficult biliary access were found to have a lower rate of post-ERCP pancreatitis than the late precut group 5.4% (10/185) vs 14.1% (19/135). 9 …”
Section: Precut Needle Knife Papillotomy/ Suprapapillary Needle-knifementioning
confidence: 99%